2016
DOI: 10.1158/0008-5472.can-15-2350
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Alterations in Enzyme-Coding and Cancer-Causing Genes Reprogram Tumor Metabolism

Abstract: Somatic copy number alterations frequently occur in the cancer genome affecting not only oncogenic or tumor suppressive genes, but also passenger and potential codriver genes. An intrinsic feature resulting from such genomic perturbations is the deregulation in the metabolism of tumor cells. In this study, we have shown that metabolic and cancer-causing genes are unexpectedly often proximally positioned in the chromosome and share loci with coaltered copy numbers across multiple cancers (19 cancer types from T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…Furthermore, we did not detect many somatic mutations in secreting or nonsecreting pituitary tumors, supporting the findings of prior reports (22,38,39). SCNAs reflect DNA damage and genomic instability and occur in normal tissue and cancerous tumors (23,40). Our observation of genome instability with sparse SNV/InDel mutations was previously described in nonproliferating, terminally differentiated cells, which are highly metabolically active (41,42).…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, we did not detect many somatic mutations in secreting or nonsecreting pituitary tumors, supporting the findings of prior reports (22,38,39). SCNAs reflect DNA damage and genomic instability and occur in normal tissue and cancerous tumors (23,40). Our observation of genome instability with sparse SNV/InDel mutations was previously described in nonproliferating, terminally differentiated cells, which are highly metabolically active (41,42).…”
Section: Resultssupporting
confidence: 91%
“…It is therefore tempting to speculate that evolution of cancer might be driven by phenotypic traits, and that oncogenes and tumour suppressors might be selected for their efficiency in regulating these metabolic changes. In line with this hypothesis, a recent study found that metabolic and cancer-causing genes undergo co-altered somatic copy number variation 28 , indicating that alteration of cancer-associated genes is often linked with metabolic rewiring. These findings may catalyse a better understanding of the role of dysregulated metabolism in cancer and provide novel means to stratify patients based on their metabolic features.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, many phenotypes are polygenic, apparent only when pathways involving multiple genes are perturbed. SNPs are not the only genetic variants that need to be considered; for example, gene copy number variation can cause functionally important perturbations in metabolism (Reiter et al, 2016; Sharma et al, 2016). For these reasons, studies advancing precision nutrition need to focus on developing computational and mathematical modeling of the underlying complex genetics and then develop algorithms for calculating the integrated effects of multiple genetic contributions that together predict metabolic inefficiencies.…”
Section: Genetic Variation As a Source Of Nutrition-relevant Metabolimentioning
confidence: 99%